A Translanguaging as a Culturally Responsive Practice: EFL Teachers’ Insights in Indonesian Classrooms - Fatus, Fatimatus Sadiyah; Irmayani; Buyun Khulel; Syifa Khuriyatuz Zahro (Universitas Nahdatul Ulama Surabaya, 2026)
This study explores translanguaging as a culturally responsive pedagogical practice in Indonesian EFL classrooms by examining its classroom enactment, the pedagogical reasoning underlying its use, and the challenges teachers face in implementing it. Adopting a qualitative descriptive design, the study analysed classroom observations, instructional documents, lesson plans, and teachers’ written reflections to capture naturally occurring instructional practices without relying primarily on participant self-reports. The findings reveal that EFL teachers employ translanguaging strategically to facilitate meaning-making processes, including clarifying instructions, explaining complex vocabulary and grammatical concepts, managing classroom interactions, and enhancing student engagement. Teachers’ pedagogical reasoning was inferred from recurring instructional patterns observed across lessons—specifically, when and for what purposes teachers shifted between languages—from the alignment between lesson plans, instructional materials, and classroom enactment, as well as from teachers’ reflective documents that articulated rationales for particular language choices. Triangulation of these data sources indicates that teachers’ translanguaging practices are guided by efforts to promote comprehension, reduce learners’ anxiety, and create inclusive learning environments that acknowledge students’ linguistic and cultural identities. However, the findings also demonstrate that institutional expectations of English-only instruction, limited professional preparation in multilingual pedagogy, diverse student linguistic backgrounds, and prevailing societal ideologies privileging English proficiency constrain the consistent implementation of translanguaging. Overall, the study concludes that translanguaging constitutes a pedagogically grounded and culturally responsive practice shaped by teachers’ professional judgment and contextual realities. The study underscores the need for clearer policy support and targeted professional development to strengthen multilingual pedagogical practices in Indonesian EFL contexts.